ONLINE AND SEMI-ONLINE MENTORING METHODS: COMMUNITY EMPOWERMENT STRATEGIES DURING THE NEW NORMAL PANDEMIC - Elly Lestari Rustiati; Elsa Virnarenata; Priyambodo Priyambodo; Salih Alimudin; Dwi Asmi; Edi Santoso; Yanti Yulianti; Dian Neli Pratiwi; Erdi Suroso (Ann Publisher, 2024)
Community stewardship can be done directly. Direct interaction is commonly applied, appreciated, and easy to communicate. During the COVID-19 pandemic, direct interaction and visits are almost impossible due to activity limitations and social distancing. Online and semi-online interaction can be applied by inviting community limited representatives combined with the online method. Initiation on online communication is introduced. This project was conducted in companionship and training in Braja Harjosari and Labuhan Ratu VII, East Lampung. Following the introduction of the online and semionline methods, local people can apply and share their knowledge of the new normal paradigm.